1988
DOI: 10.1111/j.1524-4725.1988.tb03590.x
|View full text |Cite
|
Sign up to set email alerts
|

Nonsurgical Treatments for Skin Cancer: Retinoids and α‐Interferon

Abstract: Retinoids, the natural and synthetic analogs of vitamin A, and alpha-interferon have been used effectively in the treatment of certain cutaneous premalignancies and malignancies. Retinoids have shown impressive activity against premalignant disorders of the skin (actinic keratoses, keratoacanthoma, epidermodysplasia verruciformis) and of other epithelial sites (oral leukoplakia, cervical dysplasia). In established basal cell skin cancers, topical retinoid treatment has produced a complete response rate of 33%,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

1990
1990
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(9 citation statements)
references
References 64 publications
0
8
0
1
Order By: Relevance
“…[3][4][5][6][7][8][9][10][11][12][13][14][17][18][19][20][21][22] Certain important comparisons can be made between the present trial and our previous phase II trial demonstrating the activity of only 13cRA and IFN␣ in advanced skin SCC. The major activity occurred in locally advanced disease: overall response and CR rates of 67% (eight of 12) and 33% (four of 12), respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5][6][7][8][9][10][11][12][13][14][17][18][19][20][21][22] Certain important comparisons can be made between the present trial and our previous phase II trial demonstrating the activity of only 13cRA and IFN␣ in advanced skin SCC. The major activity occurred in locally advanced disease: overall response and CR rates of 67% (eight of 12) and 33% (four of 12), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…34 These studies provide insights into the mechanisms of the RA and IFN components of the present study's regimen. 3,4 Cisplatin (75 to 100 mg/m 2 every 3 to 4 weeks) for skin SCC has been involved in only two previous series with greater than 10 patients. 3,4 Cisplatin (75 to 100 mg/m 2 every 3 to 4 weeks) for skin SCC has been involved in only two previous series with greater than 10 patients.…”
Section: Discussionmentioning
confidence: 99%
“…In 1988, Grob et al [12] reported the same results in 8 patients treated with IFN alfa-2a. Lippman et al [ 16] utilized intralesional IFN in 7 patients with BCC; in 6 of these patients, a complete response was achieved. More recently, Cornell et al 117] treated 172 patients with ulcerative and superficial BCC with IFN alfa-2b.…”
Section: Resultsmentioning
confidence: 99%
“…All ofthese treatments are generally effective against CTCL, but cannot cure all patients, especially those with late-stage or aggressive disease. Therefore, several new effective modalities have been applied to CTCL, including biological response modifiers (BRMs), such as interleukin-2 (IL-2) and interferons (IFNs) (4,5), combination BRM therapy using IL-2 and IFN, IL-2 and tumor necrosis factor (TNF) or BRMs, and chemotherapeutics for patients with advanced malignancy (6). These latter combination therapies, BRMs and chemotherapeutics, are reported to be more effective than BRM therapy alone (6).…”
Section: Introductionmentioning
confidence: 99%